"System of hunger": Understanding causal disaster vulnerability of indigenous food systems. (January 2020) - Jackson, Guy; McNamara, Karen E.; Witt, Bradd
Abstract: The exposure of vulnerable food systems to hazards often leads to outcomes such as food insecurity. In order to prevent such food insecurity, it is critical to understand the causal factors – or root causes – of vulnerability, particularly in a world of increasing risk. As such, this paper develops and implements a food system causal disaster vulnerability framework within the Bedamuni tribe of Papua New Guinea. Although changing, Bedamuni livelihoods remain centred on subsistence swidden agriculture, hunting, and gathering. The framework developed here considers food systems as socioecological systems that through, for example, ecosystem use, provision, and social institutions should ideally provide food security along with other forms of social and cultural welfare. As detailed in the paper, disaster vulnerability is considered a function of exposure (temporal and spatial), susceptibility (as historical, socio-human, psychological, economic, environmental, physical, cultural, and governance dimensions), livelihood resilience (as knowledge, power and participation, capabilities, assets, and social capital) and absorptive, adapttive, and transformational capacities. The study is based on in-depth mixed methods fieldwork undertaken in 25 villages throughout the Bedamuni territory and incorporates established ethnographic approaches (e.g., participant observation, garden and disaster transect walks, and interviews) and a novel culturally appropriate approach (e.g., 31 "longhouse stories" lasting 1–3 h). The study reveals the main drivers of increasing vulnerability relate to historical, ecological, social, and psychological dimensions of susceptibility and declining adaptive capacity. The need for transformational change is suggested but is hindered by declining self-efficacy, inertia and a lack of knowledge of how to address factors such as population growth, declining land productivity, climate change, and increasing garden pests and diseases. Taken together with high exposure to El Niño droughts (e.g., 1971/2, 1982/3, 1997, 2015/16) and earthquakes (e.g., 1950, 2018), disaster vulnerability is concerningly high and participants suggest is increasing. This paper is an empirically grounded argument for using causal approaches that look beyond outcomes to identify drivers of vulnerability in food systems. The framework and empirical evidence presented provides researchers, NGOs, and policy makers guidance and entry points for reducing vulnerability and increasing the resilience of marginalised Indigenous food systems in Papua New Guinea and potentially beyond. Highlights: Develops and implements a causal disaster vulnerability framework for Indigenous food systems. Food systems are conceptualised as socioecological systems. Identifies high exposure to El Niño droughts and earthquakes. Identifies historical, psychological, and environmental dimensions of susceptiblity and declining adaptive capacity are central to understanding vulnerability. Provides entry points to reduce vulnerability and increase resilience in Indigenous food systems.